Treasurer's Experience In Applying Average Effective Rates For Income Tax 21 - Moh Faisol; Norsain Norsain; Imam Rofiqi (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This study aims to understand the experience of treasurer taxpayers in withholding taxes based on TER PPh 21 at KPP Pratama ZA. Methodology/approach: The researcher uses an interpretive approach with a phenomenological method. The researcher interviewed 11 treasurer taxpayers from different institutional backgrounds, such as government agencies, state-owned enterprises, hospitals, private companies, and foundations. Data analysis uses spiral data analysis. Findings: Income Tax 21 withholding using TER provides convenience to treasurers because it is supported by the integrated e-bupot 21/26 feature. Practical implications: This study underscores the ease and efficiency of treasured taxpayers in withholding Income Tax 21 is significantly enhanced by information technology, thereby providing practical insights for tax professionals and individuals interested in tax withholding practices. Originality/value: This study understands the experience of the treasurer in withholding Income Tax 21 using the average effective rate (TER) with spiral data analysis